Erosion and flooding-threats to coastal Infrastructure in the Arctic : a case study from Herschel Island, Yukon Territory, Canada - Radosavljevic, Boris; Lantuit, Hugues; Pollard, Wayne; Overduin, Paul; Couture, Nicole; Sachs, Torsten; Helm, Veit; Fritz, Michael (Universität Potsdam, 2020)
Arctic coastal infrastructure and cultural and archeological sites are increasingly vulnerable to erosion and flooding due to amplified warming of the Arctic, sea level rise, lengthening of open water periods, and a predicted increase in frequency of major storms. Mitigating these hazards necessitates decision-making tools at an appropriate scale. The objectives of this paper are to provide such a tool by assessing potential erosion and flood hazards at Herschel Island, a UNESCO World Heritage candidate site. This study focused on Simpson Point and the adjacent coastal sections because of their archeological, historical, and cultural significance. Shoreline movement was analyzed using the Digital Shoreline Analysis System (DSAS) after digitizing shorelines from 1952, 1970, 2000, and 2011. For purposes of this analysis, the coast was divided in seven coastal reaches (CRs) reflecting different morphologies and/or exposures. Using linear regression rates obtained from these data, projections of shoreline position were made for 20 and 50 years into the future. Flood hazard was assessed using a least cost path analysis based on a high-resolution light detection and ranging (LiDAR) dataset and current Intergovernmental Panel on Climate Change sea level estimates. Widespread erosion characterizes the study area. The rate of shoreline movement in different periods of the study ranges from −5.5 to 2.7 m·a⁻¹ (mean −0.6 m·a⁻¹). Mean coastal retreat decreased from −0.6 m·a⁻¹ to −0.5 m·a⁻¹, for 1952–1970 and 1970–2000, respectively, and increased to −1.3 m·a⁻¹ in the period 2000–2011. Ice-rich coastal sections most exposed to wave attack exhibited the highest rates of coastal retreat. The geohazard map combines shoreline projections and flood hazard analyses to show that most of the spit area has extreme or very high flood hazard potential, and some buildings are vulnerable to coastal erosion. This study demonstrates that transgressive forcing may provide ample sediment for the expansion of depositional landforms, while growing more susceptible to overwash and flooding. : Postprints der Universität Potsdam : Mathematisch-Naturwissenschaftliche Reihe, 996